Automotive service inspection, maintenance, repair - Gilles, Tim 1951- (Delmar Cengage Learning, 2012)
Contains the knowledge and skills necessary for a student to be successful in a number of automotive careers. This text covers eight major course areas of automotive technology, introducing shop management and theories of vehicle systems operations with step-by-step procedures for trouble-shooting and repairing automobiles.